IMPACT OF PHYSICAL ACTIVITIES UNDERTAKEN USING VR ON MENTAL WELL BEING, FOR FOREIGN LANGUAGE TEACHERS (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2025)
Mental well-being and language learning anxiety play a crucial role in the effectiveness and productivity of foreign language teaching. In recent years, growing attention has been given to the psychological health of educators; however, limited research has explored innovative approaches to supporting mental well-being, particularly in Central Asian contexts. This qualitative study explores the impact of virtual reality (VR)–based physical activities on the mental well-being of foreign language teachers at a university level. The study aimed to (1) examine teachers’ understanding of their mental well-being, (2) identify their experiences, barriers, and facilitators related to engagement in regular physical activity, and (3) investigate their perceptions of physical activities undertaken using immersive VR.Data were collected through semi-structured baseline and follow-up interviews. Participants took part in five VR-based physical activity sessions over a two-week period. Thematic analysis revealed that participants conceptualized mental well-being in diverse ways but commonly identified physical activity as a key strategy for managing stress, anxiety, depression, and mood. Traditional activities such as walking, running, stretching, and meditation were frequently reported. Findings from follow-up interviews indicated that although VR-based physical activities were initially challenging due to their novelty, they were perceived as engaging, enjoyable, and effective in temporarily improving mood and reducing anxiety. Participants reported increased immersion and distraction from daily stressors during VR sessions.While the positive effects were short-term and VR was not viewed as a replacement for conventional physical activity, it was considered a valuable and innovative complementary tool. The study acknowledges limitations related to small sample size and lack of data saturation and recommends further large-scale qualitative and mixed-method studies.